The characteristics of beta 2-glycoprotein I-dependent anticardiolipin antibody and blood coagulation status in subjects with classical biological false-positive syphilis reactions - Shen, Xu; Liu, Dan; Lin, Yong; Zhu, Xiao-Zhen; Lin, Li-Rong; Tong, Man-Li; Liang, Xian-Ming; Liu, Li-Li; Yang, Tian-Ci; Niu, Jian-Jun (International immunopharmacology, 2018)
Anticardiolipin antibody (ACA) includes beta2-glycoprotein I-dependent (β2-GPI-dependent) and β2-GPI-independent forms. The appearance of β2-GPI-dependent ACA and its association with blood coagulation have never been investigated in subjects with classical biological false-positive syphilis reactions (CBFP). In total, 146 CBFP subjects, 465 syphilis patients and 64 presumed antiphospholipid antibody syndrome (pAPS) patients were enrolled, and β2-GPI-dependent ACA IgA/IgG/IgM and anti-β2-GPI IgA/IgG/IgM antibodies were detected via chemiluminescence assay. Conventional blood coagulation indices were measured to analyze their associations with these autoantibodies. In current study, the positive rate of β2-GPI-dependent ACA in CBFP subjects was 22.60%, which was significantly higher than that in syphilis patients (3.87%) (P < 0.001) and similar to that in pAPS patients (32.81%) (P = 0.119). The predominant autoantibody isotypes were IgG in CBFP subjects and pAPS patients and IgM in syphilis patients. Positive autoantibody rates were independent of rapid plasma reagin titers. CBFP and pAPS subjects had longer prothrombin times (P < 0.001) and activated partial thromboplastin times (APTTs, P < 0.001) but lower fibrinogen concentrations (P = 0.022) and platelet counts (P < 0.001) than syphilis patients. APTTs were prolonged in CBFP, syphilis and pAPS subjects with positive autoantibodies compared with those in subjects with negative autoantibodies (P < 0.05). In conclusion, ACAs in CBFP and syphilis subjects are heterogeneous; β2-GPI-dependent ACA constitutes a significant proportion of ACAs in CBFP subjects, while β2-GPI-independent ACA predominates in syphilis patients. CBFP subjects are more prone to blood coagulation disorders than syphilis patients, and these autoantibodies may impact the intrinsic coagulation cascade in CBFP subjects, similar to pAPS patients. •Anticardiolipin antibodies (ACAs) in CBFP and syphilis subjects are heterogeneous.•β2-GPI-dependent ACA accounts for a significant proportion of ACA in CBFP subjects.•No associations exist between RPR titers and positive β2-GPI-dependent ACA in CBFP.•CBFP subjects are more prone to coagulation disorder than are syphilis patients.